Pengaruh Penggunaan Media Scrapbook terhadap Motivasi Belajar Siswa Kelas IV Sekolah Dasar - Almi, Ridwan; Sutarna, Nana (Jurnal Likhitaprajna, 2024)
This research is based on the problems that occur in the learning process, namely the lack of student motivation in the learning process and teachers need learning media that can motivate students in the learning process. One way to overcome this problem is to have learning media that is interesting fun and can motivate students in learning. The purpose of this study was to determine the effect of scrapbook media on student learning motivation in class IV IPAS learning SDN 2 Sakerta Timur, The type of research used in this study is quantitative with a one shot case study research design. The research subjects were grade IV students totaling 15 people. This study uses data collection techniques using questionnaires. the analysis used in this study is in the form of questionnaire tests, validation tests, prerequisite tests and hypothesis tests. The results showed that the results of the questionnaire test of learning motivation of class IV students obtained the lowest score of 75 and the highest score was 97.9. While the average of the learning motivation score of grade IV students is 88.7. In addition, based on the hypothesis test, the calculation obtained a Sig. 2-tailed value of 0.00<0.05. So it can be concluded that scrapbook media has an effect on learning motivation in IPAS learning for fourth grade students of SDN 2 Sakerta Timur in the 2023/2024 school year. The results of this study presented can be concluded that student learning motivation can increase after being given therapy in the form of scrapbook learning media.